Recent progress in electrochemical decomposition of hydrogen sulfide for sulfur recovery and hydrogen production - Chen, Yanjun; Wen, Ming; Ding, Tong; Fan, Rui; Liu, Qisong; Liu, Zongshe; Peng, Zicheng (Frontiers in Chemistry, 2025)
Hydrogen sulfide (H2S) generated by industrial processes (such as petroleum refining, natural gas purification, and coal processing) is a highly toxic and corrosive gas, which is detrimental to human health and environment. Electrocatalytic decomposition of H2S for simultaneous desulfurization and hydrogen production has emerged as a promising approach to addressing environmental pollution whilst achieving valuable utilization of H2S. Currently, there are two pathways for electrochemical decomposition of H2S, namely, direct and indirect decomposition. For the direct pathway, H2S is electrocatalytically oxidized into sulfur at anode using electrocatalysts. However, this approach is hindered by electrocatalyst deactivation due to sulfur passivation. Conversely, the indirect pathway effectively prevents the anodic sulfur passivation by introducing soluble redox couples as mediators, transferring H2S oxidation reaction from electrode to liquid phase. In this regard, the selection of redox mediators is critical since it affects H2S oxidation efficiency, sulfur purity, and overall decomposition voltage. In light of the challenges associated with above-mentioned electrochemical H2S decomposition techniques, this review presents recent advancements in strategies to mitigate anodic sulfur passivation for direct decomposition method, as well as the development of redox mediators and process optimization for indirect decomposition method. Meanwhile, a comparative analysis of characteristic and reaction mechanism of both approaches is provided. Finally, perspectives are given on the current challenges and future research directions in the field of electrocatalytic H2S splitting technology.